Refined construction of semi-provincial hydrogeological models using hierarchical modeling: A case study in Western Shandong Province, China - Guangjun Ji; Zizhao Cai; Xiaobo Tan; Tao Wang; Chuanqi Wang; Qiuxiao Xu; Bo Zhou; Yang Cui (Journal of Hydrology: Regional Studies)
Study region: Western Shandong Province, China, covering an area of 83,700 km², is a study area that contains various representative hydrogeological conditions. Study focus: The development of accurate and detailed large-scale hydrogeological models remains a significant challenge, with limited scientific and effective solutions available. To mitigate that challenge, a refined building method for regional hydrogeological models based on hierarchical modeling idea was proposed. In this framework, each preceding model constrains the subsequent one. Additionally, a systematic design for structural and attribute models was conducted before modeling, based on hydrogeological conditions and data distribution. This ensures precise characterization of geological objects while minimizing data requirements. Calculation methods for predicting groundwater resource storage variables and single-well water inflow were explored based on hydrogeological attribute models. New insights for the region: The hydrogeological structure and its internal attributes at the regional scale were described in detail using the aforementioned methods. The prediction results of groundwater storage variables and single-well water inflow based on attribute models may improve forecasting accuracy to some extent. These findings provide a valuable reference framework for the efficient and accurate construction of large-scale hydrogeological models and promote the further application of 3D geological modeling in hydrogeological computations.